Determinants of Nursing Service Quality: The Influence of Community Health Center Management Functions - Sri Wahyuni; Dwi Indah Iswanti; Tri Ismu Pujiyanto; I Made Moh. Yanuar Saifudin; Helena Alalag (Universitas STRADA Indonesia, 2026)
Background: The managerial capacity of community health center leaders in Indonesia remains limited, while the quality of nursing services depends heavily on how well core management functions are carried out. Purpose: This study aimed to determine the influence of community health center management functions, namely planning, mobilization and implementation, and supervision, on the quality of nursing services, and to identify the most dominant function. Methods: A quantitative observational study with a cross-sectional design was conducted at the Malinau Seberang Community Health Center, North Kalimantan, Indonesia, in 2025. A total sampling of 87 health workers completed Likert-scale questionnaires measuring the three management functions and service quality. Results: Chi-square tests showed significant associations between planning (p=0.007), mobilization and implementation (p=0.007), and supervision (p=0.006) and the quality of nursing services. Multiple logistic regression confirmed that all three functions significantly influenced service quality (p<0.001), with planning showing the largest Exp(B) value (0.0135) and identified as the most dominant determinant. These estimates should be interpreted with caution, however, since the outcome was highly skewed toward the good category and the resulting odds ratios were very small. Conclusion: These findings strengthen the evidence that integrated community health center management is key to improving nursing service quality. Health center leaders should prioritize structured, data-driven planning, supported by coordinated implementation and routine supervision, particularly in remote and border areas.